Senescence and senolytics in cardiovascular disease: Promise and potential pitfalls. (September 2021) - Owens, W Andrew; Walaszczyk, Anna; Spyridopoulos, Ioakim; Dookun, Emily; Richardson, Gavin D.
Highlights: Studies have demonstrated that senescence contributes to the pathophysiology of several age-related cardiovascular diseases. Senolytics eliminate senescent cells in cardiovascular tissues and prevent or reverse disease progression. While this data is encouraging, questions remain regarding the potential short and long-term detrimental effects of senolytic mediated apoptosis. Abstract: Ageing is the biggest risk factor for impaired cardiovascular health, with cardiovascular disease being the cause of death in 40 % of individuals over 65 years old. Ageing is associated with an increased prevalence of atherosclerosis, coronary artery stenosis and subsequent myocardial infarction, thoracic aortic aneurysm, valvular heart disease and heart failure. An accumulation of senescence and increased inflammation, caused by the senescence-associated secretory phenotype, have been implicated in the aetiology and progression of these age-associated diseases. Recently it has been demonstrated that compounds targeting components of anti-apoptotic pathways expressed by senescent cells can preferentially induce senescence cells to apoptosis and have been termed senolytics. In this review, we discuss the evidence demonstrating that senescence contributes to cardiovascular disease, with a particular focus on studies that indicate the promise of senotherapy. Based on these data we suggest novel indications for senolytics as a treatment of cardiovascular diseases which have yet to be studied in the context of senotherapy. Finally, while the potential benefits are encouraging, several complications may result from senolytic treatment. We, therefore, consider these challenges in the context of the cardiovascular system.